2008
DOI: 10.1093/intimm/dxn056
|View full text |Cite
|
Sign up to set email alerts
|

Progressive divergent shifts in natural and induced T-regulatory cells signify the transition from undifferentiated to definitive connective tissue disease

Abstract: The objectives of the study is to determine clinical signs and distribution of peripheral T-cell subsets, B cells and T regulatory cells in patients with undifferentiated connective tissue disease (UCTD) and during the development toward well-established connective tissue diseases (CTD). The methods include 46 patients with UCTD were followed and investigated for differentiation into defined CTDs for 2 years. Cell subsets were determined on the basis of cell surface markers, intracellular cytokine production b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
19
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 27 publications
1
19
1
1
Order By: Relevance
“…Based on these findings we assume that the regulation of immune responses is defective and the suppressor activity towards autoimmune processes is diminished. Additionally, we have recently reported that nTreg cells have an important controlling role in the development of systemic autoimmune diseases, namely in the transition from the undifferentiated to the definitive CTD stage (6).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these findings we assume that the regulation of immune responses is defective and the suppressor activity towards autoimmune processes is diminished. Additionally, we have recently reported that nTreg cells have an important controlling role in the development of systemic autoimmune diseases, namely in the transition from the undifferentiated to the definitive CTD stage (6).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous work we revealed the overproduction of interferon (IFN)-g, produced by T-helper (Th)1 cells, and a decreased number of natural CD4+CD25 high Foxp3+ regulatory T cells (nTregs) in patients with UCTD (6). A subset of interleukin (IL)-17-producing helper T cells (Th17 cells) distinct from Th1 or Th2 cells have been shown to play an important role in the induction of tissue inflammation and autoimmunity (7)(8)(9).…”
mentioning
confidence: 99%
“…In these patients, the assessment of Treg cells showed that the percentage and absolute number of CD4+CD25 bright FoxP3+, natural Tregs were diminished in UCTD patients compared with healthy controls, while the number of CD4+IL-10+, inducible Tregs was increased [18]. This progressive divergent shift in natural and induced T-regulatory cells clearly predicted the transition from the undifferentiated connective tissue disease to a well-established systemic autoimmune disease [18].…”
mentioning
confidence: 95%
“…As a natural follow-up to these findings, we previously investigated the regulatory T cell pool of patients with UCTD [18]. In these patients, the assessment of Treg cells showed that the percentage and absolute number of CD4+CD25 bright FoxP3+, natural Tregs were diminished in UCTD patients compared with healthy controls, while the number of CD4+IL-10+, inducible Tregs was increased [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation